Republic of Croatia : Second Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
Croatia continues to enjoy economic growth, price stability, and rising international reserves under the Stand-By Arrangement. Executive Directors commended this and stressed the need for prudent macroeconomic policies, structural reforms, fiscal consolidation, and tight monetary policy. They appreciated partial privatization of the state-owned oil company and strengthening of the financial supervision. They also emphasized the need to focus on restructuring and privatization of public enterprises to sustain high rates of economic growth and advance the prospects of Croatia's European Union accession.